Platformized Media Ecology: Reconfiguring Cinematic and Broadcast Ecosystems in the Age of Streaming - Perpetua Ogechi Aondover (PT Agung Media Publisher, 2026)
The rapid expansion of streaming platforms has fundamentally transformed cinematic and broadcast ecosystems, extending their influence beyond technological innovation toward comprehensive changes in industrial organization, cultural production, audience behavior, and media governance. Although previous studies have examined streaming from perspectives such as convergence culture, political economy, cultural globalization, and platformization, these approaches remain fragmented and insufficient to explain the multidimensional complexity of contemporary media transformation. This study aims to develop an integrated conceptual framework, termed Platformized Media Ecology, to explain how streaming platforms reconfigure cinematic and broadcast ecosystems in the digital age. Employing a qualitative conceptual research design, the study synthesizes scholarly literature from Media Ecology, Political Economy of Communication, Cultural Globalization, and Platformization through thematic synthesis and conceptual analysis. The findings reveal three major contributions. First, streaming has transformed media ecosystems beyond technological disruption by restructuring production systems, distribution mechanisms, audience engagement, regulatory arrangements, and cultural circulation. Second, platform governance has become the dominant organizing logic of contemporary audiovisual industries through algorithmic recommendation systems, behavioral data analytics, subscription-based business models, and digital infrastructures that increasingly shape content visibility and industrial decision-making. Third, the study proposes Platformized Media Ecology as an integrated theoretical framework that conceptualizes streaming platforms as ecological infrastructures connecting technological environments, industrial organization, cultural globalization, audience practices, and governance systems.